2018
DOI: 10.1007/s11033-018-4346-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of microsatellite loci for the endangered vermetid gastropod Dendropoma lebeche using Illumina MiSeq next generation sequencing technology

Abstract: Dendropoma petraeum, considered the primary vermetid reef-building species in the Mediterranean, has recently been shown to be a species complex of at least four cryptic species. These species have highly restricted, non-overlapping distributions, causing concern for their conservation status. To better study the genetic diversity of these populations, we selected one of these species, Dendropoma lebeche (Templado et al. in Mediterr Mar Sci 17(1):13-31, 2016), which is restricted to the western Mediterranean, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In addition to being highly informative, this newly generated set of SSR markers retrieved overall diversity parameters consistent with values reported for other marine gastropods [ 64 , 76 , 77 ]. Deviations from HWE in some populations – Caloura, Pico, São Jorge, and Vigo –, are frequently reported in marine invertebrates [ 70 , 72 , 73 , 102 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition to being highly informative, this newly generated set of SSR markers retrieved overall diversity parameters consistent with values reported for other marine gastropods [ 64 , 76 , 77 ]. Deviations from HWE in some populations – Caloura, Pico, São Jorge, and Vigo –, are frequently reported in marine invertebrates [ 70 , 72 , 73 , 102 ].…”
Section: Discussionsupporting
confidence: 73%
“…During the past decades, microsatellite sets have been developed and characterized for marine gastropods, especially for abundant, commercially interesting or threatened species (e.g. [ 57 64 ]). These sets of SSR markers appear to be skewed towards large-sized genera, such as Nucella, Littorina , Buccinum , Haliotis and Concholepas .…”
Section: Introductionmentioning
confidence: 99%
“…Dendropoma lebeche species identification followed a previous study (Templado et al, 2016) where the species showed a clearly delimited geographical distribution and was highly divergent at both levels of mitochondrial and nuclear genes (Calvo et al, 2009). Twenty-three polymorphic microsatellites for G. divaricata (López-Márquez et al, 2016) and D. lebeche (López-Márquez et al, 2018), respectively, were initially tested using nested PCR (polymerase chain reaction), a method successfully applied in other species including the nemertean Malacobdella arrokeana (Alfaya et al, 2014) and the mollusc Panopea abbreviata (Ahanchédé et al, 2013).…”
Section: Genetic Analysismentioning
confidence: 99%
“…Twenty-three polymorphic microsatellites for G. divaricata (López-Márquez et al, 2016) and D. lebeche (López-Márquez et al, 2018), respectively, were initially tested using nested PCR (polymerase chain reaction), a method successfully applied in other species including the nemertean Malacobdella arrokeana (Alfaya et al, 2014) and the mollusc Panopea abbreviata (Ahanchédé et al, 2013).…”
Section: Genetic Analysismentioning
confidence: 99%
“…Studying multiple species of interest in the same group (e.g., the Mediterranean reef-building Dendropoma species; worm shells, Vermetidae; Calvo et al, 2009Calvo et al, , 2015López-Márquez et al, 2018;Templado et al, 2016), or following up an initial cryptic species report with a formal description (e.g., Chilean intertidal slipper shells, Calyptraeidae, Véliz et al, 2003Véliz et al, , 2012 illustrates the importance of continued efforts to understand a species.…”
Section: Re Sultsmentioning
confidence: 99%